The SLT equation: A tool to predict and evaluate energy savings in road tunnels with sunlight systems. (April 2017) - Peña-García, A.
Highlights: The high impact of tunnel lighting has led to many proposals to use sunlight. The choice of the most accurate requires tools to evaluate the potential savings. A general equation based on physical considerations is presented. This equation includes all the proposals up to date. Abstract: The high economical and environmental impact of tunnel lighting has led to the proposal of a wide variety of strategies to use sunlight in these infrastructures. However, the choice of the most accurate strategy for each tunnel requires reliable tools to evaluate its efficacy and estimate the potential savings before real implementation in order to decide whether it is really interesting and profitable. In spite of the increasing number of ways to complement electrical lighting with sunlight during daytime, the only way up to date to really foresee which one is better for one given tunnel is the use of mockups or simulations that cost time and money. In this work, a general equation based on physical considerations and covering a vast variety of situations is presented. The deduction of the equation departs from the two main philosophies proposed or implemented up to date and converges in one general expression which is applied to some examples.